SISTEM INFORMASI PRODUKSI PADA PT. WANAPOTENSI NUSA BERBASIS WEB - Ricky Giovanni Putra Tanjaya; Dedi Trisnawarman (Jurnal Ilmu Komputer dan Sistem Informasi, 2023)
PT Wanapotensi Nusa is a company engaged in the processing of logs. Recording of production carried out by PT Wanapoten Nusa when this journal was made was still using the manual method, making it difficult for the company to analyze and also make decisions on production data. Against the background of these problems, a production information system was proposed to be able to store and display data. production so that it is expected to help companies to be able to facilitate access to production data. To make it easier for companies to make decisions about production data in this journal, a production recommendation method will also be discussed using the Economic Production Quantity (EPQ) which is expected to provide input in the form of production suggestions for the next month.